State ownership and climate change mitigation: Overcoming the carbon curse? - Benoit Mayer; Mikko Rajavuori (Centre for International Sustainable Development Law (CISDL), 2022)
The role that States can play in promoting climate change mitigation extends beyond the regulation of private actors. States are important economic actors in their own right. State-owned enterprises (SOEs) dominate sectors which are critical to a transition towards a carbon-neutral economy – particularly so in emerging economies. States have sometimes used their ownership policies to induce efforts towards climate change mitigation; they should always use this opportunity. SOEs can demonstrate the economic viability of incremental and structural reforms at the scale of a corporation. They are a chance for governments to lead by example. The framework for non-market approaches to sustainable development should further explore and raise awareness on the role that State ownership policies play in climate change mitigation.